Perception Student Regarding Historical Material Controversy in Shaping Reasoning Critical Students at SMA Negeri 1 Pekalongan - Sulistiyo, Alfian (Universitas Negeri Semarang, 2019)
The implementation of learning controversial history is crucial for enhancing student understanding and developing their critical reasoning skills. This study aims to identify how teachers handle controversial material, explore teachers' historical learning models, and describe students' perceptions of controversial historical content in shaping their critical reasoning abilities. Using a descriptive qualitative method, the research was conducted at SMA Negeri 1 Pekalongan, employing in-depth interviews, observation, and document review as data collection techniques. The study results reveal that students hold a positive and optimistic view towards teaching history when it involves controversial material. They believe that such an approach makes the subject more engaging and significantly contributes to developing their critical thinking skills. Teachers at SMA Negeri 1 Pekalongan utilize various historical learning models to present controversial topics effectively, fostering a classroom environment where students are encouraged to question, analyze, and form reasoned conclusions about historical events. This method improves their understanding of history and equips them with essential skills for evaluating different perspectives and arguments, ultimately promoting a more nuanced and critical approach to learning.